Livelihood Development and Poverty Alleviation by Indian Farm Forestry Development Cooperative Limited - Singh, S P; Dixit, S P (Indian Farming, 2017)
The Indian Farm Forestry Development Cooperative limited with its Corporate Social Responsibility approch help Creates an enabling environment for the poor to access new opportunities and develop and enhance resource base essential for leading a dignified life through sustainable community institutions.